2019
DOI: 10.3390/ijerph16020275
|View full text |Cite
|
Sign up to set email alerts
|

Root and Shoot Biomass Growth of Constructed Floating Wetlands Plants in Saline Environments

Abstract: Constructed Floating Wetlands (CFWs) are increasingly being used globally in freshwater environments such as urban lakes and ponds to remove pollutants from urban stormwater runoff. However, to date there has been limited research into the use and performance of these systems in saline environments. This study compared the root and shoot biomass growth and nutrient uptake of five different plant species, Chrysopogon zizanioides, Baumea juncea, Isolepis nodosa, Phragmites australis and Sarcocornia quinqueflora,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…1000 mM). The drastic reduction in plant performance at zero salinity indicates that S. quinqueflora is an obligate halophyte as reported by Sanicola et al (2019).…”
Section: Discussionsupporting
confidence: 69%
“…1000 mM). The drastic reduction in plant performance at zero salinity indicates that S. quinqueflora is an obligate halophyte as reported by Sanicola et al (2019).…”
Section: Discussionsupporting
confidence: 69%
“…Thus, the two more resistant and more promising plant species to cope with this environment, S. maritima and S. perennis, seem to be the most suitable species for future FWI applications in highly saline water bodies. Sanicola et al [14] reported that a plant from the same genus (Sarcocornia quinqueflora) was the one with the better root biomass growth in saltwater (rather than in freshwater) among the other four wetland plant species tested in their FWI mesocosm studies. Moreover, Calheiros et al [39] used Sarcocornia fruticosa for highly saline wastewater treatment, in a constructed wetland, where this species also demonstrated a high resilience.…”
Section: Evaluation Of Plant Establishment and Developmentmentioning
confidence: 99%
“…Wang et al 2015;Olguín et al 2017;Afzal et al 2019) and even fewer in saline environments (e.g. Sanicola et al 2019). Also Colares et al (2020) conclude in their comprehensive review and bibliometric analysis that although floating wetlands have been employed all over the world, most studies remain on laboratory or pilot scale.…”
Section: Introductionmentioning
confidence: 99%